Young British muslims : identity, culture, politics and the media - Kabir, Nahid Afrose
Based on 216 in-depth interviews of Muslims in Britain, examines how British Muslim youths and young adults, 15-30 years old, define their identities, their values and their culture and whether these conflict either with those of their parents or with the dominant non-Muslim British culture.